Production Electricity power by solar pond using Organic Rankine Cycle (Damascus University Journal for engineering sciences, 2023)
Solar pond are a form of solar collectors that collect and store solar energy in the form of heat. Solar pond could be used as a low-temperature heat source to generate power. In this research, a study was conducted to generate an electrical capacity of 1 MW through the use of a solar pond at the climatic conditions of the city of Damascus using the Organic Rankine Cycle (ORC), and considering water as the heat transfer fluid from the solar lake to the operating medium within the organic Rankine cycle, and determining the required area. The possibility of using different operating fluids and the performance of the organic Rankine cycle was then studied in order to determine the most suitable working conditions for power generation from the solar pond. The results of the study indicated that the area of ​​the lake to obtain the required capacity is approximately 11,000 m2 using the R245fa operating fluid with a thermal efficiency of 10%, while the efficiency according to the second thermodynamic law is 56%. It was also found through the study that the largest area required for the solar pond is when using R134a and R12 refrigerants, while the least area is when using R11 followed by R141b, and that the largest possible power is obtained when using R218 as an operating fluid, and it was found by studying the working conditions of a cycle Increasing the condensing temperature leads to a decrease in the required area of ​​the solar pond and an increase in the thermal yield of the organic Rankine cycle.
Keywords: solar pond; Organic Rankine Cycle; low source temperature